TIPOLOGI KEPRIBADIAN TOKOH PADA FILM GEZZ AND ANN KARYA NADHIFA ALLYA TSANA - Linda Eka Pradita; Siti Roqidah; Ulfah Kusumawati; Tiara Anggerdyah; Mukhibatur Rohmah; Bekti Wulandari (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Film is a popular visual media that can be watched by various ages according to category. The film presents an interesting story with many building elements. Building elements include many things, one of which is the character's personality typology. Personality typology classifies humans in several ways, namely extroverted and introverted personalities. The research entitled "Tipologi Kepribadian Tokoh Film Gezz and Ann Karya Nadhifa Allya Tsana" raises the typology or depiction of the characters in the film Geez and Ann which is based on the theory of Carl Gustav Jung. The method used is a qualitative method which includes theory that can provide clear views and descriptions. The data collection in this study was assessed using the note-taking method. The results of the study show that there are two personality traits, namely extrovert and introvert. This extrovert personality includes five points, namely: activity, sociability, risk taking, impulsiveness, expressiveness. Furthermore, introverted personality is divided into four points, namely: introverted thoughts, introverted feelings, introverted sensing, and introverted intuition. Keywords: Extrovert, Film, Introvert, Personality Typology.